(untitled) (Medical Forum Monthly, 2020)
Objective: The objective of this study was to compare clomiphene citrate and Letrozole in patients with polycystic ovarian syndrome in terms of monomolecular development. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at the Gynae Unit 1 Outpatient department, Holy Family Hospital Rawalpindi from January 2019 to December 2019. Materials and Methods: The patients fulfilling the inclusion /exclusion criteria were divided into two groups by lottery method. Group A was given clomephene citrate 100 mg as a single dose from day 2 to day 5 of menstrual cycle. Group B was given 5 mg letrozole as a single dose from day 2 to day 5 of menstrual cycle. The patients were followed by transvaginal scan for follicular tracking on day 11 and 13 of cycle. This ultrasound was conducted by PGT 4 0r SR. Monofollicular formation was observed on TVS. Results: In group A, PCOS was diagnosed in 30.67% patients by oligomenorhea, 32% by weight gain, hirsuitism, 21.33% by increased LH levels and 16% by ultrasound. In group B, PCOS was diagnosed in 33.33% patients by oligomenorhea, 32% by weight gain, hirsuitism, 18.67% by increased LH levels and 16% by ultrasound. Monofollicural formation was observed in 57.33% patients in group A and in group B Monofollicural formation was found in 78.67% patients. In group A, there were 49.33% patients in which primary infertility was detected and 50.67% patients in which secondary infertility was found. In group B, there were 54.67% patients in which primary infertility was detected and 45.33% patients in which secondary infertility was found. By using t-test, there was no significant difference of age in both groups having p-value = 0.49. There was no significant difference found of marriage duration in both groups having p-value = 0.86. Significant difference of parity was found in both groups having p-value = 0.05. By using chi-square test, there was significant association found between study groups and monofollicular formation. Monofollicular formation was significantly lower in group A having p-value = 0.005. There was not significant association found between age and monofollicular formation having p-value = 0.775. Marriage duration was not significantly associated with monofollicular formation having p-value = 0.085. Parity was not significantly associated with monofollicular formation having p-value = 0.475. Conclusion: Letrozole is better as compared to Clomiphene citrate in terms on mono follicular development in patients with PCOs. Effect modifiers have not significant association with mono follicular formation.